2020
DOI: 10.1177/1535370220975351
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of SARS-CoV-2 reveals local viral evolution in Ghana

Abstract: The confirmed case fatality rate for the coronavirus disease 2019 (COVID-19) in Ghana has dropped from a peak of 2% in March to be consistently below 1% since May 2020. Globally, case fatality rates have been linked to the strains/clades of circulating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) within a specific country. Here we present 46 whole genomes of SARS-CoV-2 circulating in Ghana, from two separate sequencing batches: 15 isolates from the early epidemic (March 12–April 1 2020) and 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Our previous genomic study showed evidence of undetected community spread likely caused by asymptomatic individuals 28 . Of note, nearly 80% of people who were seropositive did not report significant COVID-19 symptoms (Figure 3), confirming that SARS-CoV-2 infections in Ghana are predominantly asymptomatic, consistent with reported global trends 8 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our previous genomic study showed evidence of undetected community spread likely caused by asymptomatic individuals 28 . Of note, nearly 80% of people who were seropositive did not report significant COVID-19 symptoms (Figure 3), confirming that SARS-CoV-2 infections in Ghana are predominantly asymptomatic, consistent with reported global trends 8 .…”
Section: Discussionmentioning
confidence: 95%
“…As such, it was not surprising that the socioeconomic divide in prevalence observed in Phase I had mostly disappeared and even appeared reversed by Phase IV. Importantly, Phase IV was the first time the modal surveyed age group (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) also demonstrated model seropositivity (24.9%). This trend mimicked hospitalisation and test positivity records since December 2020 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By April 4 th , positive cases who had neither travel history nor known contact with confirmed cases, were detected, implying local transmission. To estimate COVID-19 community spread in Ghana, over a 7-month period, we randomly screened for IgM and IgG antibodies against SARS-CoV-2 in people at various public places in Accra (National capital, where >50% of reported cases occur), Kasoa (a densely-populated town in the Central Region, and a COVID-19 transmission hotspot [27] and which shares a border with Accra), Cape Coast (Central Regional capital), Akropong (a small town in the Eastern Region, a 15-minute drive away from Accra), Navrongo (a small town in the Upper East Region, which hosts a public university and a government Health Research Centre) and Bolgatanga (the Upper East Regional capital) (Figure 1). A questionnaire administered during the study collected demographic data as well and evaluated the COVID-19 knowledge, attitudes and perceptions (KAP) of study participants.…”
Section: Introductionmentioning
confidence: 99%
“…However, specific allocation of funds to institutions to conduct research and generate the local evidence to guide the national response was not obvious and scientists used internal resources to support the response. The limited activities included the modelling of the spread of the epidemic coordinated by the Science Section of the Ghana Academy of Arts and Sciences, the sequencing of the virus circulating in Ghana 4 by Noguchi Memorial Institute for Medical Research and the West African Centre for Cell Biology of Infectious Pathogens of the University of Ghana and their collaborators.…”
mentioning
confidence: 99%